2018
DOI: 10.1021/acs.analchem.8b00204
|View full text |Cite
|
Sign up to set email alerts
|

Levamisole: a Common Adulterant in Cocaine Street Samples Hindering Electrochemical Detection of Cocaine

Abstract: The present work investigates the electrochemical determination of cocaine in the presence of levamisole, one of the most common adulterants found in cocaine street samples. Levamisole misleads cocaine color tests, giving a blue color (positive test) even in the absence of cocaine. Moreover, the electrochemical detection of cocaine is also affected by the presence of levamisole, with a suppression of the oxidation signal of cocaine. When levamisole is present in the sample in ratios higher than 1:1, the cocain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 33 publications
2
56
0
Order By: Relevance
“…Jong et al . (2018) investigated the reasons for this overlapping or suppression of the peaks and showed that this process is not related with interactions between the molecules in bulk solution (formation of complexes or adducts), but by the electrochemical processes at the electrode surface (electrode passivation or adsorption of oxidation products) . The BR buffer solution pH 8.0 was chosen for further experiments, since provided higher oxidation currents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Jong et al . (2018) investigated the reasons for this overlapping or suppression of the peaks and showed that this process is not related with interactions between the molecules in bulk solution (formation of complexes or adducts), but by the electrochemical processes at the electrode surface (electrode passivation or adsorption of oxidation products) . The BR buffer solution pH 8.0 was chosen for further experiments, since provided higher oxidation currents.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, this process was applied for LEV determination in a street cocaine sample. On the other hand, the same behavior was not observed for COC, which probably is not related to the deconvolution process, but to matrix effect caused by the presence of LEV, as reported in the literature .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this study was to develop a new analytical method combining SPE and mixed‐mode LC coupled to MS/MS for the determination of COC and its related compounds in wastewater. The analytes selected were the parent drug, its metabolites BE and COE, the pyrolytic products AE and AEME, and levamisole (LEV), one of the main pharmaceuticals used in the adulteration of COC hydrochloride . To the best of our knowledge, this is the first application of RP ion‐exchange mixed‐mode LC for the determination of drugs of abuse.…”
Section: Introductionmentioning
confidence: 99%